2021
DOI: 10.1177/02656590211004666
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a training video on the shared reading behaviours of caregivers and children

Abstract: Despite evidence supporting the implementation of book sharing interventions, few studies have examined the value of providing caregiver training in these contexts. This study draws on the quantitative findings of a larger project that employed a non-randomized comparison group crossover repeated measures design as part of a mixed research approach. The goal of the study was to determine the outcome of a caregiver training video on the book sharing behaviours of 40 caregiver–child dyads in an impoverished peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The benefits of shared book reading for children’s early language and literacy development have been widely and extensively researched (Coetzee et al, 2021 ; Shahaeian et al, 2018 ; Vally et al, 2015 ). Book sharing in the first six years of a child’s life has been linked with promising (Shahaeian et al, 2018 ).…”
Section: Benefits Of Shared Book Reading and The Role Of The Speech-l...mentioning
confidence: 99%
See 4 more Smart Citations
“…The benefits of shared book reading for children’s early language and literacy development have been widely and extensively researched (Coetzee et al, 2021 ; Shahaeian et al, 2018 ; Vally et al, 2015 ). Book sharing in the first six years of a child’s life has been linked with promising (Shahaeian et al, 2018 ).…”
Section: Benefits Of Shared Book Reading and The Role Of The Speech-l...mentioning
confidence: 99%
“…Children’s early language and literacy development were found to benefit substantially from book sharing intervention, and Vally et al ( 2015 ) surmised that the positive effects that were observed in their study were attributable to improved parents’ mediation skills, which had been developed through training. A study by Coetzee et al ( 2021 ) investigated the impact of a short caregiver training video on the shared reading behaviours of caregivers and children and found a significant improvement in caregiver and children’s shared book reading behaviours after exposure to the training video. The use of training videos as effective and cost-effective intervention is supported by this and other studies (e.g., Lloyd & Robertson, 2012 ; Hsin & Cigas, 2013 ).…”
Section: Benefits Of Shared Book Reading and The Role Of The Speech-l...mentioning
confidence: 99%
See 3 more Smart Citations